Prey Impact Localization Enabled by Material and Structural Interaction in Spider Orb Webs. Issue 3 (11th January 2022) - Dal Poggetto, Vinícius F.; Bosia, Federico; Greco, Gabriele; Pugno, Nicola M.
Abstract: Spider webs are mechanical systems able to deliver an outstanding compromise between distinct requirements such as absorbing impacts and transmitting information about vibration sources. Both the frequency information and amplitude of input signals can be used by the spider to identify stimuli, aided by the mechanical filtering properties of orb webs. In this work, a numerical model based on nonlinear stress–strain constitutive relations for spider silk is introduced to investigate how the spider orb web allows spiders to detect and localize prey impacts. The obtained results indicate how the orb web center relative transverse displacements, produced by local resonance mechanisms, are used for precise localization, while nonlinear stress stiffening effects improve prey sensing. Finally, it is also shown that, although beneficial, a large number of radial threads may not be necessary for prey localization. Abstract : A numerical model considering silk nonlinear material behavior is introduced to investigate how spiders can locate prey impacts in orb webs. Results indicate that the relative displacements perceived at the orb web center can be used for precise prey localization, which is further improved by stress stiffening effects, and with a precision not limited by the number of radial threads.